2014
DOI: 10.1245/s10434-014-3507-y
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Recurrence After Therapeutic Lateral Neck Dissection for Primary Papillary Thyroid Cancer

Abstract: These results provide useful information regarding the clinical outcomes after therapeutic lateral neck dissection for primary PTC and can be used to identify at-risk patients who need aggressive treatment and intensive surveillance for postoperative recurrence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
33
1
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(43 citation statements)
references
References 24 publications
6
33
1
1
Order By: Relevance
“…As supporting data, in a subsequent publication of the same group, the response rate of intermediate-risk cN1b patients to initial therapy was approximately 85% (12). In another series involving N1bM0 patients, the recurrence rate ranged from 15-20% (13)(14)(15)(16)(17)(18), while this rate was approximately 10% in the present series. We attribute this apparent difference to the fact that the present study excluded cN1b patients who additionally exhibited incomplete tumor resection and extensive extrathyroid invasion (pT4) [high risk according to ATA (1)].…”
Section: Last Assessmentsupporting
confidence: 77%
“…As supporting data, in a subsequent publication of the same group, the response rate of intermediate-risk cN1b patients to initial therapy was approximately 85% (12). In another series involving N1bM0 patients, the recurrence rate ranged from 15-20% (13)(14)(15)(16)(17)(18), while this rate was approximately 10% in the present series. We attribute this apparent difference to the fact that the present study excluded cN1b patients who additionally exhibited incomplete tumor resection and extensive extrathyroid invasion (pT4) [high risk according to ATA (1)].…”
Section: Last Assessmentsupporting
confidence: 77%
“…Previous studies investigating the outcomes of lateral neck dissection for PTC have reported variable rates of recurrence. 18,19 In one study, the 1-, 3-, and 5-year disease-free survival rates were 94.4, 88.0, and 85.5 %, respectively. 18 Another recent study reported an overall recurrence rate of 18 % (11/61) during a median follow-up of 20 months (range 1-109 months).…”
Section: Discussionmentioning
confidence: 98%
“…Distant metastasis was diagnosed using whole-body iodine scintigraphy, chest computed tomography (CT), or whole-body. 18 F-fluorodeoxyglucose positron emission tomography/CT and confirmed by serial imaging or biopsy. In the present study, recurrence was defined as structural recurrence identified on imaging studies regardless of serum Tg levels but not as biochemical recurrence with an elevated serum Tg level and without clinical evidence of structural disease.…”
Section: Surgery and Pathologic Examinationmentioning
confidence: 95%
See 1 more Smart Citation
“…Variables predicting lateral recurrences in this setting are: male gender, aggressive histology, number on metastatic nodes and T4-off thyroglobulin levels >4 ng/ml [28]. Previous incomplete surgery ('berry picking') may also be a cause of recurrence.…”
Section: Recurrence In the Lateral Neckmentioning
confidence: 99%